Wegener Granulomatosis: Otologic Manifestation as First Symptom - Costa, Carla Fabiane da; Polanski, Jose Fernando (International Archives of Otorhinolaryngology, 2015)
Introduction Wegener granulomatosis is a systemic vasculitis affecting small and medium-sized vessels of the upper and lower respiratory tract and kidneys.Objective To describe a case of Wegener disease with atypical manifestation.Resumed Report We describe the case of a 50-year-old woman with chronic otitis media and sensorineural hearing loss as the primary symptoms, without other manifestations.Conclusion In cases of acute ear manifestations with or without hearing loss and with poor response to usual treatments, Wegener granulomatosis should be included among the possible etiologies. After adequate diagnoses and treatment of this rare disease, there was favorable evolution.
Keywords: Wegener granulomatosis; otitis media; hearing loss